The Role of Family Function and Support to Nutritional Status in Autistic Children - Muhammad Khotibuddin; Riska Shellia (Universitas Muhammadiyah Yogyakarta, 2022)
The role of the family is substantial in determining the nutritional status of children. However, not many studies have revealed this role in autistic children in Indonesia. This study aims to assess the role of family function and family support for the nutritional status of autistic children in Yogyakarta. This study used a cross-sectional design to observe at least 14 children divided into three groups: autistic-overweight, autistic-normal, and non-autistic-normal. The APGAR score measured the family function, while family support was measured by a questionnaire consisting of 5 aspects: information, respect, instrumental, emotional, and social. The difference test between the three groups used the Anova test. Total family support in the autistic-overweight group (73.17±4.45) was lower than autistic-normal (80.6±3.36) and non-autistic (78.33±3.21). This difference was significant between autistic-overweight and autistic-normal (p 0.022), but not with the non-autistic group. Furthermore, there was no difference in family function (APGAR score) between the three study groups. There was less family support among autistic-overweight children.